Інвестиційне забезпечення відтворення екосистем - Луців, О.В. (Економіка природокористування і охорони довкілля, 2013)
У статті досліджено основні складові та функції природного капіталу. Обґрунтовано доцільність проведення комплексної економічної оцінки екосистемних послуг. Запропоновано напрями інвестування для попередження та зменшення деградації екосистем. The necessity of the application of ground of the sustainable development based on increasing investment in ecosystems reproduction is proved. The anthropogenic changes of ecosystems in «brown» economy contributed to economic growth, but it has been caused the ecosystem degradation. The basic components and functions of natural capital are examined; the classification of ecosystem services by their functionality is considered in the article. Conducting the comprehensive economic valuation and economic differentiation of ecosystem services as a prerequisite for investing in natural capital is grounded.
The necessary condition for reducing the negative consequences of ecosystem services degradation was concluded\ and to prevent them is embedding considerable investments in natural capital and environmental infrastructure, that can be highly profitable, bring additional benefits, create new jobs, achieve social development goals and not harm the environment.